Surface composition dependent ligand effect in tuning the activity of nickel–copper bimetallic electrocatalysts toward hydrogen evolution in alkaline - Wei, Chao (2021)
Exploring efficient and low-cost electrocatalysts for hydrogen evolution reaction (HER) in alkaline media is crit-ical for developing anion exchange membrane electrolyzers. The key to a rational catalyst design is understanding the de-scriptors that govern the alkaline HER activity. Unfortunately, the principles that governs alkaline HER performance remain unclear and are still under debate. By studying the alkaline HER at a series of NiCu bimetallic surfaces, where the electronic structure is modulated by ligand effect, we demonstrate that alkaline HER activity can be correlated with either the calculated or the experimental-measured d band center (an indicator of hydrogen binding energy) via a volcano-type relationship. Such correlation indicates the descriptor role of d band center, and this hypothesis is further supported by the evidence that com-bining Ni and Cu produces a variety of adsorption sites, which possess near-optimal hydrogen binding energy. Our finding broadens the applicability of d band theory to activity prediction of metal electrocatalysts and may offer an insightful under-standing of alkaline HER mechanism.